Microbiome Changes in Children Treated under General Anesthesia for Severe Early Childhood Caries: Pilot Study - Tal Ratson; Nurit Dagon; Sigalit Blumer; Nir Sterer (MDPI AG, 2022)
A full-mouth radical dental treatment under general anesthesia is a common approach for treating severe early childhood caries (S-ECC). However, previous study showed recurrence of the disease in 80% of cases within 12 months. The aim of the present study was to examine the changes in microbial composition of the dental biofilm of these children following treatment. Dental biofilm samples from five children (mean age 45.4 ± 10.1 months) were taken before and three months after treatment and analyzed for microbial composition using Next Generation Sequencing of the microbial DNA extracted from these samples. Although some reductions in the abundance of caries-pathogenic bacteria (e.g., Streptococcus mutans, Streptococcus sobrinus, Rothia dentocariosa and Scardovia wiggisiae) were seen in the post-treatment follow up samples, these reductions were for the most part not statistically significant, and these bacteria remained well above detection levels. Taken together, the results of the present pilot study suggest that the dental treatment alone is not enough to reduce the caries risk status of these children and that a more comprehensive approach should be considered.